新型机加工弹簧静压状态下的应力集中研究 - 王立超; 周燕飞 (Jixie qiangdu)
The stress concentration at the end of spiral groove is very serious during the static tension and compression of the new machined spring,which has a great influence on the strength and fatigue life of the spring.The influence of spring basic parameters on the stress concentration coefficient was analyzed by ANSYS software,and the theoretical criterion for the existence of stress concentration in machined springs is determined.The effects of tangential stress release hole on compression deformation and stress concentration coefficient were investigated; Based on the strength theory and bending theory of curved beam,the formula of maximum equivalent stress without stress concentration was deduced.The results show that when the ratio of the width of the spiral groove to the pitch is less than 0.5,stress concentration occurs in machined springs with the middle diameter between 15 mm ～ 35 mm.The stress concentration can be basically eliminated by cutting stress release hole at the end of spiral groove and controlling its size to be close to the height of rectangular section.The error between the equivalent stress value of the inner ring and the simulation value is less than 3%.It provides an important reference for the subsequent engineering design and application of the new spring.